What's in a name? The three genealogies of the social in social epigenetics. (March 2020) - Louvel, Séverine
Social epigenetics – the study of the epigenetic mechanisms through which social environments become biologically embodied – epitomizes recent claims that the boundaries between the natural and the social sciences should be reduced. Relying on a bibliometric study and on a qualitative analysis of publications in social epigenetics, this article investigates how this research area defines and operationalizes the social dimensions that may have an impact on health status and disease risk. The article also addresses how the social sciences engage with social epigenetics. First, the article traces social epigenetics back to five epistemic backgrounds – two in animal research (on social defeat and early-life adversity) and three in human studies (on trauma, early-life nutrition and social adversity over the life-course). Second, it outlines the quest for epigenetic markers of social environments, and the associated expectations and controversies. Third, it analyses the three modes of engagement of the social sciences with human studies in social epigenetics: rejection (social epigenetics trapped in the quest for a 'social brain'); warning and call for responsibility (social epigenetics has shifted from socioeconomic contexts to individual behaviors); and support and active contribution (social epigenetics may strengthen social studies of health). This article argues that recent developments in social epigenetics could strengthen this third mode of engagement and expand the scope of interdisciplinary collaboration between the natural and the social sciences.